On properties of functions from Lizorkin-Triebel-Morrey type spaces - Najafov, A.M.; Gasimova, A.M. (Український математичний вісник, 2018)
We have introduced new functional spaces of the Lizorkin–Triebel–Morrey type, and a Sobolev-type inequality is proved. We have also shown that the generalized derivatives of functions from this spaces satisfy the generalized Holder condition.